Efecto de la temperatura en la biología y comportamiento de Diglyphus begini (Ashmead, 1904) (Hymenoptera: Eulophidae), un ectoparasitoide de Liriomyza huidobrensis (Blanchard, 1926) (Diptera: Agromyzidae) - Garcia, J.R. (Universidad Ricardo Palma, 2014)
The effect of temperature on the biology of Diglyphus begini (Ashmead, 1904) (Hymenoptera: Eulophidae) an ectoparasitoid of Liriomyza huidobrensis (Blanchard, 1926) (Diptera: Agromyzadae) and its potential as a biological control agent, were studied under laboratory conditions (12L: 12D) at six constant temperatures (10, 15, 20, 25, 30 and 35 °C) and environmental temperature. Temperature had a deep influence on the development of immature and longevity, reproduction and sex ratio of D. begini adult, which developed within the range of 10 ° to 30 °C. Nonlinear equations described the development, survival and oviposition dependent of temperature for D. begini, and allowed the development of a global phenology model to constant temperatures and simulation of D. begini population parameters reached the maximum rate of reproduction and total fertility, as well as, the maximum finite rate of increase (1.12 females/female/day) and the shorter double time (6.1 days) at temperatures between 24 and 26 °C. The simulation of phenology model to fluctuating temperatures indicates that the population of D. begini potentially could be increased with a finite rate of 1.02 females/female/day at an average generation time of 22.2 days and a doubling time of the population of 30.7 days. The population model based on global temperature of D. begini allows the prediction of potential growth population and its seasonal dynamics in different agro-ecological zones. The paralyzation activities exerted by females of D. begini on leafminer larvae contributed an additional 42% mortality, showing their true potential in the natural control of L. huidobrensis, which makes it a good candidate for biological control of miners within a strategy of integrated pest management.